Drohobycz - księżycowe miasto = Drohobych - a lunar city - Ruszczyńska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is an attempt to intertextual look at the memoir novel by Andrzej Chciuk "The Moon Earth. The second story about the Principality of Balak" in the perspective of referring to the poem by Kazimierz Wierzyński "The Moon". In the above ranking, the category of locality is important, with a special shift towards the city landscape and a specific imaginary space.
Keywords: memory; city landscape; imaginary space; small homeland; pamięć; krajobraz miejski; przestrzeń wyimaginowana; mała ojczyzna